Peningkatan Kinerja Sumber Daya Manusia Usaha Mikro Kecil dan Menengah di Desa Mentor, Kecamatan Sumberasih, Kabupaten Probolinggo - Hyllda Annisa Aurora; Sri Muljaningsih; Mohammad Wahed (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The small and medium-sized business sector plays a very important role in building the community's economy. In addition to having a strategic meaning for development, small and medium enterprises also function as a means to equalize the results of development that have been achieved. Performance issues are an important issue. Therefore, additional efforts are needed to disseminate it and one of the potential obstacles that will be faced is the fact that there are still many employees who lack the ability in accordance with the fields they are engaged in. In this day and age, with the rapid development of increasingly sophisticated technology, every individual is required to be able to explore all the human resources they have to support our performance so that it will greatly affect the implementation of tasks every day.